Konsep Poligami Perpektif Amina Wadud dan M. Quraish Shihab - Qonita Azzahra; Nurhayati; Aulia Fitria Ramadhani (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
Polygamy is a pretty hot topic these days, especially because of the social media factor. Discussions about polygamy attracted much attention, caused debate and gave rise to a fairly lengthy debate, among them by contemporary Mufashirs, Amina Wadud and M. Quraish Shihab for example. This article uses the type of descriptive-analysis research to describe the data collected in this research and focus on library research. (library research). Amina Wadud who came from the West and M. Quraish Shihab from a learned Muslim family gave birth to different concepts of polygamy. Amina Wadud tends to reject polygamy with the argument that this practice is not in line with the concept of gender equality and does not support the formation of a loving family as the Quran expects. While M. Quraish Shihab gives arguments in favour of polygamy on fair terms.